The effect of lactic exercises on some physical and functional variables of football players - Nayyef, Muayad nawfal; Abd, Zeyad Hameed; Hasan, Dunya Ali Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to know some of the physical and functional variables of soccer players (beginners)through the influence of lactic tolerance exercises, and the researchers used the experimental method byconducting a (pre-post) test to a sample of (20) players emerging from local clubs and were chosenintentionally and the most important results were An increase in the percentage of improvement inphysical abilities between (3.28%, 16.98%) and an increase in the percentage of improvement infunctional variables between (3.076% and 12.322%) .The researchers recommend using lactic toleranceexercises in the football training program to delay fatigue and raise the level of lactic tolerance infootball.